The Effectiveness of Cognitive Therapy for Overcoming Post Traumatic Stress Disorders in Adolescent Post Physical and Sexual Violence and its Relevance with Mental Health - Kurniawan, Didik; Syah, Ahmad Maujuhan; Ismanto, Hadi; Bradford, Snyder (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Traumatic experiences in childhood and adolescence based on 65 international studies show that almost 20% of women and 8% of men experience sexual experiences before the age 18. Regarding physical violence in the West and European countries, ranging from 3.6% to 16.3% . In Indonesia alone cases of violence against men and women aged 13-17 years ranged from 13.5% with the dominance of the victims were women. The literature method used is the search for information from several sources of articles, books, journals, which are in accordance with their relation to the problems studied in the discussion of this article. Children and adolescents who experience sexual and physical violence will certainly create trauma or symptoms of PTSD (Post Traumatic Stress Disorder). an imprint that he will carry with him to old age. The right therapy strategy will certainly be faster and more effective to restore their mental health. Several studies have shown that CBT (cognitive behavior therapy) is effective in reducing PTSD symptoms.